Effects of Propolis Impregnation on Polylactic Acid (PLA) Scaffolds Loaded withWollastonite Particles against Staphylococcus aureus, Staphylococcus epidermidis, and Their Coculture for Potential Medical Devices (2023)
Several diseases and injuries cause irreversible damage to bone tissues, which may require partial or total regeneration or replacement. Tissue engineering suggests developing substitutes that may contribute to the repair or regeneration process by using three-dimensional lattices (scaffolds) to create functional bone tissues. Herein, scaffolds comprising polylactic acid and wollastonite particles enriched with propolis extracts from the Arauca region of Colombia were developed as gyroid triply periodic minimal surfaces using fused deposition modeling. The propolis extracts exhibited antibacterial activity against Staphylococcus aureus (ATCC 25175) and Staphylococcus epidermidis (ATCC 12228), which cause osteomyelitis. The scaffolds were characterized using scanning electron microscopy, Fourier-transform infrared spectroscopy, differential scanning calorimetry, contact angle, swelling, and degradation. Their mechanical properties were assessed using static and dynamic tests. Cell viability/proliferation assay was conducted using hDP-MSC cultures, while their bactericidal properties against monospecies cultures (S. aureus and S. epidermidis) and cocultures were evaluated. The wollastonite particles did not affect the physical, mechanical, or thermal properties of the scaffolds. The contact angle results showed that there were no substantial differences in the hydrophobicity between scaffolds with and without particles. Scaffolds containing wollastonite particles suffered less degradation than those produced using PLA alone. A representative result of the cyclic tests at Fmax = 450 N showed that the maximum strain reached after 8000 cycles is well below the yield strain (i.e., <7.5%), thereby indicating that even under these stringent conditions, these scaffolds will be able to work properly. The scaffolds impregnated with propolis showed a lower % of cell viability using hDP-MSCs on the 3rd day, but these values increased on the 7th day. These scaffolds exhibited antibacterial activity against the monospecies cultures of S. aureus and S. epidermidis and their cocultures. The samples without propolis loads did not show inhibition halos, whereas those loaded with EEP exhibited halos of 17.42 0.2 mm against S. aureus and 12.9 0.5 mm against S. epidermidis. These results made the scaffolds possible bone substitutes that exert control over species with a proliferative capacity for the biofilm-formation processes required for typical severe infectious processes.